A Virtual Tour of a Hardly Accessible Archaeological Site: The Effect of Immersive Virtual Reality on User Experience, Learning and Attitude Change - Kyrlitsias, Christos; Christofi, Maria; Michael-Grigoriou, Despina; Banakou, Domna; Ioannou, Andri (Frontiers in Computer Science, 2020)
Some archaeological sites are not easily accessible by visitors due to mobility or geographical restrictions. Digital technology can make such sites virtually accessible and provide educational information at the same time. Towards this goal we created a digital reconstruction of the archaeological site of Choirokoitia. Given that a 3D digital reconstruction can be used along with different technologies, we designed and developed an interactive application, where users can navigate and get information about the site, for two different systems: Virtual Reality (VR) systems and desktop computers. A feasibility study was conducted where we compared aspects of the two systems, allowing the suggestion of the proper technology to be used, according to the users’ aims., The results showed higher levels of presence and more positive experience by the participants that used the VR system compared to those that used the desktop version. On the other hand, the greater learning gains were demonstrated in participants that used the desktop version compared to those who used the VR version. No differences were shown between the two groups regarding the participants’ change of attitudes toward the archaeology of Cyprus.